Prevalence of TECTA mutation in patients with mid-frequency sensorineural hearing loss - Nobuko Yamamoto; Hideki Mutai; Kazunori Namba; Noriko Morita; Shin Masuda; Yasuyuki Nishi; Atsuko Nakano; Sawako Masuda; Masato Fujioka; Kimitaka Kaga; Kaoru Ogawa; Tatsuo Matsunaga (Orphanet Journal of Rare Diseases, 2017)
Abstract Background To date, 102 genes have been reported as responsible for non-syndromic hearing loss, some of which are associated with specific audiogram features. Four genes have been reported as causative for mid-frequency sensorineural hearing loss (MFSNHL), among which TECTA is the most frequently reported; however, the prevalence of TECTA mutations is unknown. To elucidate the prevalence of TECTA mutation in MFSNHL and clarify genotype-phenotype correlations, we analyzed the genetic and clinical features of patients with MFSNHL. Methods Subjects with bilateral non-syndromic hearing loss were prescreened for GJB2 and m.1555A > G and m.3243A > G mitochondrial DNA mutations, and patients with inner ear malformations were excluded. We selected MFSNHL patients whose audiograms met the U-shaped criterion proposed by the GENDEAF study group, along with those with shallow U-shaped audiograms, for TECTA analysis. All TECTA exons were analyzed by Sanger sequencing. Novel missense variants were classified as possibly pathogenic, non-pathogenic, and variants of uncertain significance, based on genetic data. To evaluate novel possibly pathogenic variants, we predicted changes in protein structure by molecular modeling. Results Pathogenic and possibly pathogenic variants of TECTA were found in 4 (6.0%) of 67 patients with MFSNHL. In patients with U-shaped audiograms, none (0%) of 21 had pathogenic or possibly pathogenic variants. In patients with shallow U-shaped audiograms, four (8.7%) of 46 had pathogenic or possibly pathogenic variants. Two novel possibly pathogenic variants were identified and two previously reported mutations were considered as variant of unknown significance. The clinical features of patients with pathogenic and possibly pathogenic variants were consistent with those in previous studies. Pathogenic or possibly pathogenic variants were identified in 3 of 23 families (13.0%) which have the family histories compatible with autosomal dominant and 1 of 44 families (2.3%) which have the family histories compatible with sporadic or autosomal recessive. Conclusions TECTA mutations were identified in 6.0% of MFSNHL. These mutations were more frequent in patients with shallow U-shaped audiograms than those with U-shaped audiograms, and in families which have the family histories compatible with autosomal dominant than those with the family histories compatible with sporadic or autosomal recessive.